a2+b2+c2=(a+b+c)2−2(ab+bc+ac)=02−2.0=0a2+b2+c2=(a+b+c)2−2(ab+bc+ac)=02−2.0=0
Vì a2≥0;b2≥0;c2≥0a2≥0;b2≥0;c2≥0 với mọi a,b,c∈Ra,b,c∈R nên để tổng của chúng bằng 00 thì a2=b2=c2=0a2=b2=c2=0
⇒a=b=c=0⇒a=b=c=0
Khi đó:
A=(a−1)22+b12+(c−1)2014=(−1)22+012+(−1)2014=2
Lời giải:
Ta có: \(a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ac)=0^2-2.0=0\)
Vì $a^2\geq 0; b^2\geq 0; c^2\geq 0$ với mọi $a,b,c\in\mathbb{R}$ nên để tổng của chúng bằng $0$ thì $a^2=b^2=c^2=0$
$\Rightarrow a=b=c=0$
Khi đó:
$A=(a-1)^{22}+b^{12}+(c-1)^{2014}=(-1)^{22}+0^{12}+(-1)^{2014}=2$